2020
DOI: 10.3389/fonc.2020.588530
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of SHMT2 Is Associated With Poor Prognosis and Advanced Pathological Grade in Oral Squamous Cell Carcinoma

Abstract: This study focused on the expression of mitochondrial serine hydroxymethyltransferase (SHMT2) in oral squamous cell carcinoma (OSCC) and its correlation with clinical traits and the prognosis of OSCC patients. Immunochemical staining and Western blotting were used to quantify the expression of SHMT2 and related immune markers in OSCC. Using OSCC microarrays and The Cancer Genome Atlas (TCGA) database, we evaluated the association between SHMT2 and various clinical traits. We found that increased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…It has been reported that SHMT2, a key metabolic enzyme, can regulate cancer cell regulation and metabolism [ 7 ]. It is noteworthy that up-regulation of SHMT2 predicts a poor prognosis of OSCC patients [ 12 ]. This study was the first to explore the function of SHMT2 in OSCC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that SHMT2, a key metabolic enzyme, can regulate cancer cell regulation and metabolism [ 7 ]. It is noteworthy that up-regulation of SHMT2 predicts a poor prognosis of OSCC patients [ 12 ]. This study was the first to explore the function of SHMT2 in OSCC.…”
Section: Resultsmentioning
confidence: 99%
“…SHMT2 has shown prognostic and therapeutic value for many cancers, such as hepatic carcinoma, breast cancer, glioma, and thyroid cancer [ 26–29 ]. To our knowledge, SHMT2 is a key metabolic enzyme in the synthesis of glycine from serine and up-regulation of SHMT2 predicted a poor prognosis of OSCC patients [ 12 ]. However, the function of SHMT2 in OSCC is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLC3A2 could contribute to migration, invasion and proliferation and even decrease apoptosis in OSCC. Zhizhong Wu et al [ 18 ] found that serine hydroxymethyltransferase 2 (SHMT2), which serves as an independent prognostic marker, is overexpressed in OSCC, especially in advanced OSCC. SHMT2 is implicated in neoplasia and is associated with the expression of CD274 molecule (CD274), CKLF-like MARVEL transmembrane domain containing 6 (CMTM6), V-set immunoregulatory receptor (VSIR), V-set domain containing T cell activation inhibitor 1 (VTCN1), snail family transcriptional repressor 2 (SNAI2), and bone marrow stromal cell antigen 2 (BST2) in the tumor microenvironment of OSCC.…”
Section: Illustration Of Prognostic Indicators In Osccmentioning
confidence: 99%